Efektivitas Forgiveness Therapy untuk Memperbaiki Tingkat Self-Acceptance pada Wanita Penderita Kanker Payudara: Literature Review - Nur ‘Azizah Laili Anjainah; Abdul Muhid (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The number of deaths from breast cancer reached 684,996 people, which is 15.5% of the total deaths from cancer. In 2018 in Indonesia, breast cancer was ranked 7th of all types of cancer. The women with breast cancer generally do chemotherapy as a process that is believed to cure, however, chemotherapy has side effects in the form of physical and psychological. Women with breast cancer also experience more then one changes in their routine, related to the way they perceive their own bodies (body image). This literature review attempts to elucidate the effectiveness of forgiveness intervention in improve self-acceptance in females whose suffering breast cancer. A writing thecnique that uses a literature review by gathering various data from a described phenomenon in the journal, book, or some alternative type of reference that is relevant with the topic. The results obtained are forgiveness therapy has effectiveness in increasing acceptance in women with breast cancer. Keywords: Forgiveness Therapy; Self-acceptance; Breast Cancer